IMPLEMENTASI PROGRAM BINA PRIBADI ISLAM (BPI) DALAM MEMBENTUK KARAKTER ISLAMI PESERTA DIDIK DI SMPIT THARIQ BIN ZIYAD BOARDING SCHOOL: IMPLEMENTASI PROGRAM BINA PRIBADI ISLAM (BPI) DALAM MEMBENTUK KARAKTER ISLAMI PESERTA DIDIK DI SMPIT THARIQ BIN ZIYAD BOARDING SCHOOL - Firdiansyah Firdiansyah (Marifah: Jurnal Pendidikan dan Pemikiran Peradaban Islam, 2024)
Abstract This study aims to examine how the Islamic Personal Development (BPI) program is implemented to shape the Islamic character of students at SMPIT Thariq Bin Ziyad Boarding School. The research method used is a qualitative descriptive approach with data collection through observation, interviews, and documentation. Data validity through triangulation, while data analysis uses interactive data analysis models. The results of the study found that the implementation of the BPI program consists of two programs, namely the main BPI program and the supporting BPI program. BPI programs that are mainly carried out during class hours include weekly meetings, while those outside class hours include BPI Classical, Funiyah (skills), Mabit and Sports activities. Supporting programs during class hours include Tahfidz and Habituation of Morning Worship, while outside class hours include compulsory prayers 5 times in congregation, dhuha, Qur'an Camping and Adab, Camp Unit Organizers, introduction to the school environment, fasting Monday and Thursday, berinfaq, and Al-Kahfian. Keywords: Implementation, Islamic Personal Development Program, Islamic Character